Composition for temporary fixing and method for manufacturing wafer

CN122996136APending Publication Date: 2026-10-27DENKA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202580020012.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-27
Filing Date
2025-03-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0008]并且,在专利文献1中,作为要解决的课题,记载有固化速度、旋转涂布工艺适应性、耐热性、高温真空下的低释气性、剥离速度不充分,或者尤其对UV激光剥离工艺的适性也同样不充分

Benefits of technology

[0099]根据本发明,能够提供一种能够抑制照射激光起经过一定时间后的晶片与支撑部件的再粘着的临时固定用组合物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996136A_ABST
    Figure CN122996136A_ABST
Patent Text Reader

Abstract

A temporary fixing composition comprising: a polymerizable component (A) comprising a (meth)acrylate, a photoradical polymerization initiator (B), and an ultraviolet absorber (C); a ratio of a production area of carbon particles based on a specific method is 0.50% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a composition for temporary fixation and a method for manufacturing a wafer. Background Technology

[0002] In the manufacture of wafers used in electronic devices, measures are needed to prevent breakage caused by thinning during processing. One such measure involves applying a temporary fixing composition that can be peeled off after processing to the side of the wafer opposite to the surface being ground (the back side), and temporarily fixing it to a support member.

[0003] Patent Document 1 describes a temporary fixation composition containing the following (A) to (C).

[0004] (A) (Meth)acrylates containing (A-1) and (A-2) below.

[0005] (A-1) Monofunctional (meth)acrylates with alkyl side chains having 18 or more carbon atoms and a Tg of -100℃ to 60℃ for homopolymers.

[0006] (A-2) Polyfunctional (meth)acrylates

[0007] (B) Polyisobutylene polymer alone and / or polyisobutylene copolymer (C) Photoradical polymerization initiator.

[0008] Furthermore, in Patent Document 1, the problems to be solved include insufficient curing speed, adaptability to spin coating process, heat resistance, low gas release under high temperature vacuum, insufficient peeling speed, and especially insufficient adaptability to UV laser peeling process.

[0009] Existing technical documents

[0010] Patent documents

[0011] Patent Document 1: International Publication No. 2021 / 235406 Summary of the Invention

[0012] The present invention provides a temporary fixing composition capable of suppressing the re-adhesion of a wafer to a support component after a certain period of time following laser irradiation.

[0013] According to the present invention, a temporary fixing composition and a method for manufacturing a wafer are provided as shown below.

[0014] 1. A composition for temporary fixation, comprising:

[0015] Polymerizing component (A) containing (meth)acrylate.

[0016] Photoradical polymerization initiator (B), and

[0017] Ultraviolet absorber (C);

[0018] The ratio of the carbon particle generation area based on Method 1 below is 0.50% or more.

[0019] (Method 1)

[0020] A temporary fixing film, consisting of the aforementioned temporary fixing composition, is applied between a disk-shaped silicon wafer with a diameter of 150 mm and a thickness of 625 μm and a disk-shaped glass support member with a diameter of 150 mm and a thickness of 700 μm, thereby bonding the silicon wafer and the glass support member together.

[0021] Next, under a nitrogen atmosphere, a UV-LED with a wavelength of 405 nm is irradiated onto the temporary fixing film from the side of the glass support component, thereby curing the temporary fixing film to obtain a cured film, wherein the illuminance of the UV-LED is 100 mW / cm². 2 The irradiation time was 50 seconds, and the cumulative light intensity was 5000 mJ / cm². 2 .

[0022] Next, from the glass support component side, the obtained cured film is irradiated with a UV laser with a wavelength of 355nm in a scanning manner, wherein the UV laser is a YAG laser with an output of 6.5W, a spot diameter of 150μm, an irradiation spacing of 200μm, a scanning speed of 8m / s, and a frequency of 40kHz.

[0023] Next, the glass support component is peeled off from the silicon wafer, and the solidified film side surface of the central part of the glass support component is observed and photographed using an optical microscope at 20x magnification. The area (%) of the black part in each field of view is calculated using image processing software when the area of ​​one field of view of 200μm×200μm is set to 100%, and this is taken as the carbon particle generation area (%).

[0024] 2. The temporary fixation composition according to claim 1, wherein,

[0025] The carbon particles contain carbon black.

[0026] 3. The temporary fixation composition according to 1. or 2, wherein,

[0027] The carbon particle content in the temporary fixation composition is less than 1.0% by mass.

[0028] 4. The temporary fixation composition according to any one of 1 to 3, wherein,

[0029] The photoradical polymerization initiator (B) comprises one or more selected from the group consisting of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl] acetone 1-(O-acetyl oxime).

[0030] 5. The temporary fixation composition according to any one of 1 to 4, wherein,

[0031] The ultraviolet absorber (C) has one or more skeletons selected from the group consisting of benzophenone skeleton, triazole skeleton, hydroxyphenyltriazine skeleton and phenol skeleton.

[0032] 6. The temporary fixation composition according to any one of 1 to 5, wherein,

[0033] The ultraviolet absorber (C) has polymerizable functional groups.

[0034] 7. The temporary fixation composition according to 6, wherein,

[0035] The polymeric functional group is present at the end of the ultraviolet absorber (C).

[0036] 8. The temporary fixation composition according to 6 or 7, wherein,

[0037] The polymerizable functional group includes (meth)acryloyl.

[0038] 9. The temporary fixation composition according to any one of 1 to 8, wherein,

[0039] The content of the ultraviolet absorber (C) is 0.1 parts by mass or more and 20 parts by mass or less, relative to 100 parts by mass of the polymeric component (A) containing (meth)acrylate.

[0040] 10. The temporary fixation composition according to any one of 1 to 9, wherein,

[0041] The content of the polymeric component (A) containing (meth)acrylate is 50% by mass or more and 99% by mass or less relative to 100% by mass of the temporary fixation composition.

[0042] 11. The temporary fixation composition according to any one of 1. to 10., wherein,

[0043] The content of the photoradical polymerization initiator (B) is 0.1 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the polymerizable component (A) containing (meth)acrylate.

[0044] 12. The temporary fixation composition according to any one of 1. to 11., wherein,

[0045] The polymeric component (A) containing (meth)acrylate comprises one or more selected from the group consisting of monofunctional (meth)acrylates and difunctional (meth)acrylates.

[0046] 13. The temporary fixation composition according to any one of 1. to 12, wherein,

[0047] The polymeric component (A) containing (meth)acrylate comprises one or more selected from the group consisting of monofunctional alkyl (meth)acrylates having an alkyl group, aromatic (meth)acrylates, alicyclic difunctional (meth)acrylates and noncyclic difunctional (meth)acrylates.

[0048] 14. The temporary fixation composition according to 13, wherein,

[0049] The aromatic (meth) acrylate contains a component selected from 9,9-bis[4-(2-hydroxyC1-C1-C2-hydroxyethyl esters). 20 [Alkoxy]phenyl]fluorene di(meth)acrylate, 9,9-bis[4-(2-(meth)acryloyloxyC1~C 20 [alkoxy]phenyl]fluorene, C1-C 20 Alkoxylated bisphenol A di(meth)acrylate, benzyl di(meth)acrylate, 1,3-bis(2-(meth)acryloyloxy C1-C 20 One or more of the following groups: alkyl)benzene, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, nonylphenol ethylene oxide-modified (meth)acrylate and their structural isomers.

[0050] 15. The temporary fixation composition according to any one of 1. to 14, wherein,

[0051] Using an E-type viscometer, at a temperature of 23°C and a shear rate of 75s... -1 The viscosity of the temporary fixation composition, as measured below, is 100 mPa•s or more and 5000 mPa•s or less.

[0052] 16. The temporary fixation composition according to any one of 1. to 15, wherein,

[0053] When implementing method 2 below, the transmittance of the 355nm wavelength laser is less than 10.0%.

[0054] (Method 2)

[0055] Prepare two rectangular Tempax glass pieces, each 33mm × 50mm in diameter and 700μm thick. Drop 0.1g of the temporary fixation composition onto one of the pieces and clamp it with the other.

[0056] Next, the obtained laminate was irradiated with a UV-LED at a wavelength of 405 nm under a nitrogen atmosphere, thereby curing the temporary fixing composition to obtain a test piece for transmittance measurement, wherein the illuminance of the UV-LED was 100 mW / cm². 2 The irradiation time was 50 seconds, and the cumulative light intensity was 5000 mJ / cm². 2 .

[0057] Next, the transmittance of the obtained test piece was measured using a spectrophotometer at a spacing of 1.0 nm and a wavelength range of 300–800 nm.

[0058] Next, the transmittance at wavelength 355nm is read from the obtained transmittance data and set as the transmittance at wavelength 355nm.

[0059] 17. The temporary fixation composition according to any one of 1. to 16, wherein,

[0060] The peel strength P1 immediately after laser irradiation based on method 3 is above 0.01N and below 30.0N.

[0061] (Method 3)

[0062] A temporary fixing film, consisting of the aforementioned temporary fixing composition, is applied between a disk-shaped silicon wafer with a diameter of 150 mm and a thickness of 625 μm and a disk-shaped glass support member with a diameter of 150 mm and a thickness of 700 μm, thereby bonding the silicon wafer and the glass support member together.

[0063] Next, under a nitrogen atmosphere, a UV-LED with a wavelength of 405 nm is irradiated onto the temporary fixing film from the side of the glass support component, thereby curing the temporary fixing film to obtain a cured film, wherein the illuminance of the UV-LED is 100 mW / cm². 2 The irradiation time was 50 seconds, and the cumulative light intensity was 5000 mJ / cm². 2 .

[0064] Next, from the glass support component side, the obtained cured film is irradiated with a UV laser with a wavelength of 355nm in a scanning manner to obtain a laminate, wherein the UV laser is a YAG laser with an output of 6.5W, a spot diameter of 150μm, an irradiation spacing of 200μm, a scanning speed of 8m / s, and a frequency of 40kHz.

[0065] Next, within one minute after the UV laser irradiation ends, the obtained laminate is placed on the adsorption stage with the silicon wafer side facing down and fixed. An adsorption arm with three 10mm diameter suction cups attached to the glass support component is vertically pulled upward at a speed of 0.5mm / second to peel off the glass support component. The load applied to the adsorption arm when the glass support component is lifted is measured and set as the peel strength P1 (N).

[0066] 18. The temporary fixation composition according to any one of 1. to 17., wherein,

[0067] Based on method 4 below, the peel strength P2 10 minutes after laser irradiation is above 0.01N and below 50.0N.

[0068] (Method 4)

[0069] A temporary fixing film, consisting of the aforementioned temporary fixing composition, is applied between a disk-shaped silicon wafer with a diameter of 150 mm and a thickness of 625 μm and a disk-shaped glass support member with a diameter of 150 mm and a thickness of 700 μm, thereby bonding the silicon wafer and the glass support member together.

[0070] Next, under a nitrogen atmosphere, a UV-LED with a wavelength of 405 nm is irradiated onto the temporary fixing film from the side of the glass support component, thereby curing the temporary fixing film to obtain a cured film, wherein the illuminance of the UV-LED is 100 mW / cm². 2 The irradiation time was 50 seconds, and the cumulative light intensity was 5000 mJ / cm². 2 .

[0071] Next, from the glass support component side, the obtained cured film is irradiated with a UV laser with a wavelength of 355nm in a scanning manner to obtain a laminate, wherein the UV laser is a YAG laser with an output of 6.5W, a spot diameter of 150μm, an irradiation spacing of 200μm, a scanning speed of 8m / s, and a frequency of 40kHz.

[0072] Next, 10 minutes after UV laser irradiation, the obtained laminate was placed on the adsorption stage with the silicon wafer side facing down and fixed in place. An adsorption arm with three 10mm diameter suction cups attached to the glass support component was vertically pulled upward at a speed of 0.5mm / second to peel off the glass support component. The load applied to the adsorption arm when the glass support component was lifted was measured and set as the peel strength P2 (N).

[0073] 19. The temporary fixation composition according to any one of 1. to 18., wherein,

[0074] The ratio (P2 / P1) of the peel strength P2 10 minutes after laser irradiation based on Method 5 below to the peel strength P1 immediately after laser irradiation is 2.0 or less.

[0075] (Method 5)

[0076] A temporary fixing film, consisting of the aforementioned temporary fixing composition, is applied between a disk-shaped silicon wafer with a diameter of 150 mm and a thickness of 625 μm and a disk-shaped glass support member with a diameter of 150 mm and a thickness of 700 μm, thereby bonding the silicon wafer and the glass support member together.

[0077] Next, under a nitrogen atmosphere, a UV-LED with a wavelength of 405 nm is irradiated onto the temporary fixing film from the side of the glass support component, thereby curing the temporary fixing film to obtain a cured film, wherein the illuminance of the UV-LED is 100 mW / cm². 2 The irradiation time was 50 seconds, and the cumulative light intensity was 5000 mJ / cm². 2 .

[0078] Next, from the glass support component side, the obtained cured film is irradiated with a UV laser with a wavelength of 355nm in a scanning manner to obtain a laminate, wherein the UV laser is a YAG laser with an output of 6.5W, a spot diameter of 150μm, an irradiation spacing of 200μm, a scanning speed of 8m / s, and a frequency of 40kHz.

[0079] Next, within one minute after the UV laser irradiation ends, the obtained laminate is placed on the adsorption stage with the silicon wafer side facing down and fixed. An adsorption arm with three 10mm diameter suction cups attached to the glass support component is vertically pulled upward at a speed of 0.5mm / second to peel off the glass support component. The load applied to the adsorption arm when the glass support component is lifted is measured and set as the peel strength P1 (N).

[0080] Next, a laminate was obtained under the same conditions as described above. Ten minutes after UV laser irradiation, the laminate was placed on an adsorption stage with the silicon wafer side facing down and fixed in place. An adsorption arm with three 10mm diameter suction cups attached to the glass support was vertically pulled upward at a speed of 0.5mm / s to peel off the glass support. The load applied to the adsorption arm when the glass support was lifted was measured and set as the peel strength P2 (N).

[0081] Calculate P2 / P1 based on P1 and P2 calculated using the method described above.

[0082] 20. The temporary fixing composition according to any one of 1 to 19, which is capable of temporarily fixing the support member and the wafer.

[0083] 21. The temporary fixation composition according to 20, wherein,

[0084] The supporting components include glass supporting components.

[0085] 22. The temporary fixation composition according to 20 or 21, wherein,

[0086] The wafer includes a semiconductor wafer.

[0087] 23. A method for manufacturing a wafer, comprising:

[0088] In the peeling process, a structure having a support member, a cured film of the temporary fixing composition as described in any one of 1 to 22, and a wafer are irradiated from the support member side with a UV laser with a wavelength of 300 nm or more and 385 nm or less. Carbon particles are generated by decomposing at least a portion of the cured film of the temporary fixing composition, and the wafer and the support member are peeled off.

[0089] 24. A composition comprising:

[0090] Polymerizing component (A);

[0091] Polymerization initiator (B); and

[0092] Ultraviolet absorber (C).

[0093] The ratio of the carbon particle generation area based on Method 1 below is 0.50% or more.

[0094] (Method 1)

[0095] A disk-shaped film of the composition, with a diameter of 150 mm and a thickness of 50 μm, is applied between a disk-shaped silicon wafer with a diameter of 150 mm and a thickness of 625 μm and a disk-shaped glass support member with a diameter of 150 mm and a thickness of 700 μm, thereby bonding the silicon wafer and the glass support member together.

[0096] Next, under a nitrogen atmosphere, the film is irradiated with a UV-LED with a wavelength of 405 nm from the side of the glass support member, thereby curing the film to obtain a cured film, wherein the illuminance of the UV-LED is 100 mW / cm². 2 The irradiation time was 50 seconds, and the cumulative light intensity was 5000 mJ / cm². 2 .

[0097] Next, from the glass support component side, the obtained cured film is irradiated with a UV laser with a wavelength of 355nm in a scanning manner, wherein the UV laser is a YAG laser with an output of 6.5W, a spot diameter of 150μm, an irradiation spacing of 200μm, a scanning speed of 8m / s, and a frequency of 40kHz.

[0098] Next, the glass support component is peeled off from the silicon wafer, and the solidified film side surface of the central part of the glass support component is observed and photographed using an optical microscope at 20x magnification. The area (%) of the black part in each field of view is calculated using image processing software when the area of ​​one field of view of 200μm×200μm is set to 100%, and this is taken as the carbon particle generation area (%).

[0099] According to the present invention, a temporary fixing composition is provided that can suppress the re-adhesion of the wafer and the support component after a certain period of time caused by laser irradiation. Attached Figure Description

[0100] Figure 1 This is a microscope image of the cured film side surface of the central portion of the glass support component in Example 1.

[0101] Figure 2 This is a microscopic image of the cured film side surface of the central portion of the glass support component in Comparative Example 3.

[0102] Figure 3 This is a diagram illustrating the method for measuring peel strength. Detailed Implementation

[0103] The present invention will now be described according to embodiments.

[0104] In this embodiment, the term "(meth)acrylate" indicates that it includes both acrylates and methacrylates. The same applies to similar terms such as "(meth)acrylic acid".

[0105] The composition of this embodiment will be described below.

[0106] The composition of this embodiment comprises a polymerizable component (A), a polymerization initiator (B), and an ultraviolet absorber (C), and the ratio of the carbon particle generation area based on method 1 below is 0.50% or more.

[0107] (Method 1)

[0108] A disc-shaped film (150mm in diameter × 625μm in thickness) composed of a composition is applied between a disc-shaped silicon wafer (150mm in diameter × 700μm in thickness) and a disc-shaped glass support member (150mm in diameter × 700μm in thickness), thereby bonding the silicon wafer and the glass support member together.

[0109] Next, under a nitrogen atmosphere, the film was irradiated with a UV-LED with a wavelength of 405nm (illuminance of 100mW / cm²) from the glass support component side. 2 Irradiation time: 50 seconds; cumulative light intensity: 5000 mJ / cm² 2 This process solidifies the membrane, resulting in a cured membrane.

[0110] Next, from the glass support component side, the obtained cured film is irradiated with a UV laser with a wavelength of 355nm (YAG laser, output 6.5W, spot diameter 150μm, irradiation spacing 200μm, scanning speed 8m / s, frequency 40kHz) in a scanning manner.

[0111] Next, the glass support component was peeled off from the silicon wafer, and the solidified film side surface of the central part of the glass support component was observed and photographed using an optical microscope at 20x magnification. The area (%) of the black part in each field of view was calculated using image processing software with the area of ​​one field of view (200μm×200μm) set to 100%, and this was taken as the area (%) of carbon particle generation.

[0112] The preferred composition is one for temporary fixation.

[0113] 1. Composition for temporary fixation

[0114] The temporary fixation composition of this embodiment will be described below.

[0115] The temporary fixation composition of this embodiment comprises: a polymerizable component (A) containing (meth)acrylate; a photoradical polymerization initiator (B); and an ultraviolet absorber (C), wherein the ratio of the carbon particle generation area based on method 1 below is 0.50% or more.

[0116] (Method 1)

[0117] A disk-shaped temporary fixing film (150mm in diameter × 625μm in thickness) composed of a temporary fixing composition is applied between a disk-shaped silicon wafer (150mm in diameter × 700μm in thickness) and a disk-shaped glass support member (150mm in diameter × 700μm in thickness), thereby bonding the silicon wafer and the glass support member together.

[0118] Next, under a nitrogen atmosphere, the temporary fixing film was irradiated with a UV-LED with a wavelength of 405nm (illuminance of 100mW / cm²) from the glass support component side. 2 Irradiation time: 50 seconds; cumulative light intensity: 5000 mJ / cm² 2 This process solidifies the temporary fixation film, resulting in a cured film.

[0119] Next, from the glass support component side, the obtained cured film is irradiated with a UV laser with a wavelength of 355nm (YAG laser, output 6.5W, spot diameter 150μm, irradiation spacing 200μm, scanning speed 8m / s, frequency 40kHz) in a scanning manner.

[0120] Next, the glass support component was peeled off from the silicon wafer, and the solidified film side surface of the central part of the glass support component was observed and photographed using an optical microscope at 20x magnification. The area (%) of the black part in each field of view was calculated using image processing software with the area of ​​one field of view (200μm×200μm) set to 100%, and this was taken as the area (%) of carbon particle generation.

[0121] The mechanism by which the temporary fixing composition of this embodiment can suppress the re-adhesion (hereinafter, sometimes simply referred to as re-adhesion) between the wafer and the support component after a certain period of time following laser irradiation is not yet clear, but it is speculated that carbon particles generated when the temporary fixing composition of this embodiment is irradiated with light such as UV laser help to suppress re-adhesion.

[0122] <Carbon Particles>

[0123] The carbon particles of this embodiment will be described below.

[0124] From the viewpoint of further suppressing re-adhesion, the ratio of the carbon particle generation area in this embodiment based on method 1 is preferably 0.55% or more, more preferably 0.60% or more, even more preferably 0.70% or more, even more preferably 0.75% or more, even more preferably 0.80% or more, even more preferably 0.90% or more, even more preferably 1.00% or more, even more preferably 1.10% or more, even more preferably 1.20% or more. Furthermore, from the viewpoint of suppressing contamination caused by carbon particles, it is preferably 20.00% or less, more preferably 10.00% or less, even more preferably 5.00% or less, even more preferably 3.00% or less. And, from the viewpoint of suppressing re-adhesion... From the viewpoint of balancing the suppression of pollution caused by carbon particles and the suppression of pollution caused by carbon particles, it is preferable to be 0.50% or more and 20.00% or less, more preferably 0.55% or more and 20.00% or less, even more preferably 0.60% or more and 20.00% or less, even more preferably 0.70% or more and 20.00% or less, even more preferably 0.75% or more and 10.00% or less, even more preferably 0.80% or more and 10.00% or less, even more preferably 0.90% or more and 5.00% or less, even more preferably 1.00% or more and 5.00% or less, even more preferably 1.10% or more and 3.00% or less, even more preferably 1.20% or more and 3.00% or less.

[0125] There are no particular limitations on the image processing software used to calculate the area in Method 1 above; for example, Fiji, manufactured by the National Institutes of Health, can be used.

[0126] From the viewpoint of further suppressing re-adhesion, the carbon particles in this embodiment are preferably composed of carbon black.

[0127] From the viewpoint of being able to suppress pollution caused by carbon particles, the carbon particle content in the temporary fixation composition of this embodiment is preferably 1.0% by mass or less, more preferably 0.1% by mass or less, even more preferably 0.01% by mass or less, even more preferably 0.001% by mass or less, and even more preferably 0.0001% by mass or less.

[0128] That is, the temporary fixation composition of this embodiment preferably does not contain carbon particles as an admixture, and even if it contains a small amount of carbon particles as an admixture, it is preferably below the above-mentioned upper limit value.

[0129] Furthermore, the carbon particles included as admixtures in the temporary fixing composition of this embodiment can be, for example, carbon black, hard carbon, soft carbon, graphite, etc., with carbon black being the most common.

[0130] <Polymerizing component (A) containing (meth)acrylates>

[0131] Hereinafter, the polymeric component (A) containing (meth)acrylate in this embodiment will be described.

[0132] The polymerizable component (A) containing (meth)acrylate in this embodiment is preferably one or more selected from the group consisting of monofunctional (meth)acrylates and polyfunctional (meth)acrylates, more preferably one or more selected from the group consisting of monofunctional (meth)acrylates and difunctional (meth)acrylates.

[0133] The multifunctional (meth)acrylates in this embodiment refer to (meth)acrylates that are more than two-functional.

[0134] Bifunctional (meth)acrylates will be described later.

[0135] Examples of trifunctional (meth)acrylates include ethylene oxide-modified isocyanurate tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tri[(meth)acryloyloxyethyl]isocyanurate.

[0136] Examples of tetrafunctional or higher (meth)acrylates include bis(trimethylolpropane)tetra(meth)acrylate, dimethylolpropanetetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol ethoxytetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0137] The multifunctional (meth)acrylate in this embodiment can be a multifunctional (meth)acrylate monomer, a multifunctional (meth)acrylate polymer, or a mixture thereof, but preferably contains a multifunctional (meth)acrylate polymer, more preferably contains a polybutyl (meth)acrylate containing (meth)acrylate groups, and even more preferably contains a polybutyl acrylate containing acrylate groups.

[0138] Polybutyl (meth)acrylate containing (meth)acrylate groups can be manufactured, for example, by the methods described in Japanese Patent Application Publication No. 61-207478, Japanese Patent Application Publication No. 61-31330, Japanese Patent Application Publication No. 10-278207, Japanese Patent Application Publication No. 9-40741, and Japanese Patent Application Publication No. 8-357621.

[0139] In this embodiment, the weight-average molecular weight of the polyfunctional (meth)acrylate polymer is preferably 5,000 or more and 500,000 or less, more preferably 10,000 or more and 300,000 or less, even more preferably 30,000 or more and 200,000 or less, and even more preferably 50,000 or more and 100,000 or less. By keeping the weight-average molecular weight within the above range, the viscosity of the temporary fixing composition and the crosslinking density of the cured product can be set within the preferred range.

[0140] In this embodiment, the weight-average molecular weight of the multifunctional (meth)acrylate polymer is a value converted from standard polystyrene determined by gel permeation chromatography (GPC). Specifically, for example, the weight-average molecular weight is determined by using tetrahydrofuran as a solvent, a GPC system (SC-8010 manufactured by TOSOH CORPORATION), and a calibration curve prepared from commercially available standard polystyrene under the following conditions.

[0141] Flow rate: 1.0 ml / min

[0142] Set temperature: 40℃

[0143] Column structure: 1 “TSK guardcolumn MP (×L)” 6.0mm ID×4.0cm column manufactured by TOSOH CORPORATION and 2 “TSK-GELMULTIPOREHXL-M” 7.8mm ID×30.0cm (theoretical plate count 16,000 segments) columns manufactured by TOSOH CORPORATION, totaling 3 columns (overall theoretical plate count 32,000).

[0144] Sample injection volume: 100 μl (sample solution concentration 1 mg / ml)

[0145] Liquid delivery pressure: 39 kg / cm 2

[0146] Detector: RI detector

[0147] The polymerizable component (A) containing (meth)acrylate in this embodiment is preferably one or more selected from the group consisting of monofunctional alkyl (meth)acrylates having an alkyl group, aromatic (meth)acrylates, alicyclic difunctional (meth)acrylates, and noncyclic difunctional (meth)acrylates. From the viewpoint of providing a rigid structure, it is more preferably one or more selected from the group consisting of aromatic (meth)acrylates and alicyclic difunctional (meth)acrylates, and even more preferably contains aromatic (meth)acrylates.

[0148] In this embodiment, the alkyl group of the monofunctional alkyl (meth) acrylate having an alkyl group (hereinafter, sometimes simply referred to as the alkyl group of this embodiment) is preferably one or more selected from the group consisting of straight-chain alkyl, branched alkyl and alicyclic alkyl.

[0149] In this embodiment, the alkyl group is preferably an alkyl group containing 18 to 40 carbon atoms, and more preferably an alkyl group containing 18 to 32 carbon atoms. This improves the properties of the aliphatic hydrocarbons (preferably the properties of the aliphatic hydrocarbons of the entire system) in the polymerizable component (A) containing (meth)acrylate of this embodiment, thereby improving low volatility, chemical resistance, and heat resistance.

[0150] In this embodiment, the alkyl group preferably comprises one or more types selected from the group consisting of branched alkyl groups and alicyclic alkyl groups, and more preferably comprises one or more types selected from the group consisting of branched alkyl groups and cycloalkyl groups such as isostearyl, isotetracosyl (2-decyl-1-tetradecyl, etc.), and isotetracarboxyl (2-tetradecyl-1-octadecyl, etc.). This improves the compatibility of the polymerizable component (A) containing (meth)acrylate in this embodiment with other components.

[0151] The alkyl-containing monofunctional alkyl (meth) acrylate of this embodiment is preferably one or more selected from the group consisting of stearyl (meth) acrylate, isostearyl (meth) acrylate, docosyl (meth) acrylate, 2-decyl-1-tetradecyl (meth) acrylate, 2-dodecyl-1-hexadecyl (meth) acrylate and 2-tetradecyl-1-octadecyl (meth) acrylate, more preferably one or more selected from the group consisting of stearyl (meth) acrylate and isostearyl (meth) acrylate, and even more preferably isostearyl (meth) acrylate.

[0152] From the viewpoint of providing a rigid structure, the aromatic (meth)acrylate of this embodiment is preferably composed of a component selected from 9,9-bis[4-(2-hydroxyC1-C1-C2-hydroxyl group]. 20 [Alkoxy]phenyl]fluorene di(meth)acrylate, 9,9-bis[4-(2-(meth)acryloyloxyC1~C 20 [alkoxy]phenyl]fluorene, C1-C 20 Alkoxylated bisphenol A di(meth)acrylate, benzyl di(meth)acrylate, 1,3-bis(2-(meth)acryloyloxy C1-C 20One or more of the following are included in the group consisting of alkylbenzene, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, nonylphenol ethylene oxide-modified (meth)acrylate and their structural isomers, more preferably including 9,9-bis[4-(2-(meth)acryloyloxyC1-C1]... 20 The group comprises one or more of the following: alkoxy[4-(2-acryloyloxyethoxy)phenyl]fluorene and nonylphenol ethylene oxide modified (meth)acrylate, more preferably comprising one or two of the following: 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene and nonylphenol ethylene oxide modified acrylate.

[0153] From the viewpoint of providing a rigid structure, the alicyclic bifunctional (meth)acrylate of this embodiment is preferably composed of C1 to C2. 20 Alkoxylated hydrogenated bisphenol A di(meth)acrylate, 1,3-di(methacryloyloxyadamantane, tricyclic C 10 ~C 20 Alkane-diethanol di(meth)acrylate, bicyclic C5-C 20 One or more of the following groups are included in the group consisting of di(meth)acrylates and their structural isomers, more preferably including C1 to C2. 20 Alkoxylated hydrogenated bisphenol A di(meth)acrylate, more preferably comprising ethoxylated hydrogenated bisphenol A di(meth)acrylate.

[0154] The noncyclic difunctional (meth)acrylate of this embodiment is preferably composed of one or more selected from the group consisting of 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, neopentyl glycol modified trimethylolpropane di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and caprolactone modified hydroxypentanoic acid neopentyl glycol di(meth)acrylate, more preferably comprising 1,10-decanediol di(meth)acrylate.

[0155] The content of the polymeric component (A) of (meth)acrylate in the temporary fixation composition of this embodiment is preferably 50% by mass or more and 99% by mass or less relative to 100% by mass of the temporary fixation composition of this embodiment, more preferably 60% by mass or more and 99% by mass or less, even more preferably 70% by mass or more and 99% by mass or less, even more preferably 80% by mass or more and 99% by mass or less, and even more preferably 85% by mass or more and 99% by mass or less.

[0156] <Photoradical polymerization initiator (B)>

[0157] The photoradical polymerization initiator (B) of this embodiment will be described below.

[0158] The photoradical polymerization initiator (B) in this embodiment is, for example, a compound whose molecules are cleaved and split into two or more free radicals by irradiation with ultraviolet or visible light (e.g., wavelength 350-700 nm, preferably 365-500 nm, more preferably 385-450 nm).

[0159] From the perspective of balancing re-adhesion inhibition, increased reaction rate, and improved heat resistance after curing, the photoradical polymerization initiator (B) in this embodiment comprises bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, bis(n5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrolo-1-yl)-phenyl)titanium, 2-benzyl-2-dimethylamino-1-(4-morpholinylphenyl)-butane-1-one, and 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-ylphenyl) One or more of the following are selected from the group consisting of butane-1-one, 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-O-benzoyl oxime and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl] ethyl ketone 1-(O-acetyl oxime), preferably including one or more of the following selected from the group consisting of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl] ethyl ketone 1-(O-acetyl oxime), more preferably including bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.

[0160] From the viewpoint of balancing re-adhesion inhibition, reaction rate improvement, and heat resistance improvement after curing, the content of photoradical polymerization initiator (B) in the temporary fixation composition of this embodiment is preferably 0.1 parts by mass or more and 10 parts by mass or less, more preferably 0.5 parts by mass or more and 5.0 parts by mass or less, even more preferably 1.0 parts by mass or more and 3.0 parts by mass or less, and even more preferably 1.2 parts by mass or more and 2.0 parts by mass or less, relative to 100 parts by mass of the polymerizable component (A) containing (meth)acrylate in this embodiment.

[0161] <UV absorber (C)>

[0162] The ultraviolet absorber (C) of this embodiment will be described below.

[0163] From the viewpoint of re-adhesion suppression, the degree of overlap with UV laser wavelengths in the UV absorption wavelength region, and the balance of UV absorption characteristics at the same wavelength, the UV absorber (C) of this embodiment is preferably having one or more skeletons selected from the group consisting of benzophenone skeleton, triazole skeleton (preferably benzotriazole skeleton), hydroxyphenyltriazine skeleton and phenol skeleton (preferably hindered phenol skeleton), more preferably having one or more skeletons selected from the group consisting of benzophenone skeleton and triazole skeleton (preferably benzotriazole skeleton), and even more preferably having one or more skeletons selected from the group consisting of benzophenone skeleton and benzotriazole skeleton.

[0164] From the viewpoint of re-adhesion suppression, the degree of overlap with UV laser wavelengths in the UV absorption wavelength region, and the balance of UV absorption characteristics at the same wavelength, the UV absorber (C) of this embodiment is preferably composed of both a UV absorber (C) having a benzophenone skeleton and a UV absorber (C) having a benzotriazole skeleton.

[0165] The ultraviolet absorber (C) in this embodiment is preferably a polymerizable functional group.

[0166] The polymerizable functional group in this embodiment is preferably present at the end of the ultraviolet absorber (C) in this embodiment.

[0167] In this embodiment, the polymerizable functional group is preferably (meth)acryloyl.

[0168] The ultraviolet absorber (C) in this embodiment is preferably one or two selected from the group consisting of 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole (product name: RUVA-93, manufactured by Otsuka Chemical Co., Ltd.) and 2,2'-dihydroxy-4,4'-diaceryloyloxybenzophenone (product name: DAINSORB P-66, manufactured by Daiwa FineChemicals Co., Ltd.), more preferably two.

[0169] From the viewpoint of further suppressing re-adhesion, the content of the ultraviolet absorber (C) in the temporary fixation composition of this embodiment is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, further preferably 1.0 parts by mass or more, further preferably 1.5 parts by mass or more, further preferably 2.0 parts by mass or more, and further preferably 2.5 parts by mass or more, relative to 100 parts by mass of the polymeric component (A) containing (meth)acrylate in this embodiment. Furthermore, from the viewpoint of improving heat resistance and durability, 20 parts by mass is preferred. The amount is preferably 15 parts by weight or less, more preferably 10 parts by weight or less, and from the viewpoint of balancing re-adhesion inhibition, heat resistance improvement and durability improvement, it is preferably 0.1 parts by weight or more and 20 parts by weight or less, more preferably 0.5 parts by weight or more and 20 parts by weight or less, more preferably 1.0 parts by weight or more and 15 parts by weight or less, more preferably 1.5 parts by weight or more and 15 parts by weight or less, more preferably 2.0 parts by weight or more and 10 parts by weight or less, and more preferably 2.5 parts by weight or more and 10 parts by weight or less.

[0170] <Other Ingredients>

[0171] The temporary fixing composition of this embodiment may contain components other than those described above, such as solvents, defoamers, surfactants, colorants, polymerization inhibitors, stabilizers, adhesion modifiers, release agents, fillers, and other known components. The content of these other components can be set arbitrarily as needed.

[0172] <Physical Properties of Compositions for Temporary Fixation>

[0173] The physical properties of the temporary fixation composition of this embodiment will be described below.

[0174] (Viscosity)

[0175] Using an E-type viscometer, at a temperature of 23°C and a shear rate of 75s... -1 The viscosity of the temporary fixing composition of this embodiment, as measured below, is preferably 100 mPa·s or more and 5000 mPa·s or less, more preferably 500 mPa·s or more and 4000 mPa·s or less, even more preferably 1000 mPa·s or more and 3000 mPa·s or less, even more preferably 1000 mPa·s or more and 2000 mPa·s or less, and even more preferably 1100 mPa·s or more and 1500 mPa·s or less. This improves the workability when applying the temporary fixing composition of this embodiment.

[0176] (Transmittance of a laser with a wavelength of 355nm)

[0177] When implementing method 2 below, the transmittance of the 355nm wavelength laser in the temporary fixation composition of this embodiment is preferably 10.0% or less, more preferably 5.0% or less, even more preferably 1.0% or less, even more preferably 0.5% or less, and even more preferably 0.1% or less. Therefore, the laser is well absorbed by the cured material of the temporary fixation composition, thereby promoting peeling.

[0178] (Method 2)

[0179] Prepare two rectangular Tempax glass pieces (33mm × 50mm, 700μm thick), drop 0.1g of the temporary fixation composition onto one of them, and clamp it with the other.

[0180] Next, the obtained laminate was irradiated with a UV-LED with a wavelength of 405 nm (illuminance of 100 mW / cm²) under a nitrogen atmosphere. 2 Irradiation time: 50 seconds; cumulative light intensity: 5000 mJ / cm² 2 This process solidifies the temporary fixation composition, resulting in a test piece for transmittance measurement.

[0181] Next, the transmittance of the obtained test piece was measured using a spectrophotometer at a spacing of 1.0 nm and a wavelength range of 300–800 nm.

[0182] Next, the transmittance at wavelength 355nm is read from the obtained transmittance data and set as the transmittance at wavelength 355nm.

[0183] In addition, before the transmittance measurement, prepare two rectangular Tempax glass pieces (33mm×50mm, 700μm thick), add 0.1g of water to one of them, and clamp it with the other to obtain a baseline measurement test piece. Use the obtained baseline measurement test piece to measure the baseline of the spectrophotometer.

[0184] (Peel strength P1 immediately after laser irradiation)

[0185] The peel strength P1 of the temporary fixation composition of this embodiment based on method 3 immediately after laser irradiation is, for example, 0.01 N or more, and preferably 30.0 N or less, more preferably 25.0 N or less, even more preferably 20.0 N or less, even more preferably 18.0 N or less, even more preferably 16.0 N or less, even more preferably 14.0 N or less, even more preferably 12.0 N or less, even more preferably 10.0 N or less, and preferably 0.01 N or more and 30.0 N or less, more preferably 0.01 N or more and 25.0 N or less, even more preferably 0.01 N or more and 20.0 N or less, even more preferably 0.01 N or more and 18.0 N or less, even more preferably 0.01 N or more and 16.0 N or less, even more preferably 0.01 N or more and 14.0 N or less, even more preferably 0.01 N or more and 12.0 N or less, even more preferably 0.01 N or more and 10.0 N or less.

[0186] (Method 3)

[0187] A disk-shaped temporary fixing film (150mm in diameter × 625μm in thickness) composed of a temporary fixing composition is applied between a disk-shaped silicon wafer (150mm in diameter × 700μm in thickness) and a disk-shaped glass support member (150mm in diameter × 700μm in thickness), thereby bonding the silicon wafer and the glass support member together.

[0188] Next, under a nitrogen atmosphere, the temporary fixing film was irradiated with a UV-LED with a wavelength of 405nm (illuminance of 100mW / cm²) from the glass support component side. 2 Irradiation time: 50 seconds; cumulative light intensity: 5000 mJ / cm² 2 This process solidifies the temporary fixation film, resulting in a cured film.

[0189] Next, from the glass support component side, the obtained cured film is irradiated with a UV laser with a wavelength of 355nm (YAG laser, output 6.5W, spot diameter 150μm, irradiation spacing 200μm, scanning speed 8m / s, frequency 40kHz) in a scanning manner to obtain a laminate.

[0190] Next, within one minute after the UV laser irradiation ends, the obtained laminate is placed on the adsorption stage with the silicon wafer side facing down and fixed in place. The adsorption arm, which is attached to the glass support component and has three suction cups with a diameter of 10 mm, is vertically pulled upward at a speed of 0.5 mm / s to peel off the glass support component. The load applied to the adsorption arm when the glass support component is lifted is measured and set as the peel strength P1 (N).

[0191] (Peel strength P2 10 minutes after laser irradiation)

[0192] The peel strength P2 of the temporary fixation composition of this embodiment, after 10 minutes of laser irradiation based on method 4 described below, is, for example, 0.01 N or more, and preferably 50.0 N or less, more preferably 40.0 N or less, even more preferably 30.0 N or less, even more preferably 25.0 N or less, even more preferably 20.0 N or less, even more preferably 18.0 N or less, even more preferably 16.0 N or less, even more preferably 14.0 N or less, even more preferably 12.0 N or less, and even more preferably... The value is 10.0N or less, and preferably 0.01N or more and 30.0N or less, more preferably 0.01N or more and 25.0N or less, even more preferably 0.01N or more and 20.0N or less, even more preferably 0.01N or more and 18.0N or less, even more preferably 0.01N or more and 16.0N or less, even more preferably 0.01N or more and 14.0N or less, even more preferably 0.01N or more and 12.0N or less, even more preferably 0.01N or more and 10.0N or less.

[0193] (Method 4)

[0194] A disk-shaped temporary fixing film (150mm in diameter × 625μm in thickness) composed of a temporary fixing composition is applied between a disk-shaped silicon wafer (150mm in diameter × 700μm in thickness) and a disk-shaped glass support member (150mm in diameter × 700μm in thickness), thereby bonding the silicon wafer and the glass support member together.

[0195] Next, under a nitrogen atmosphere, the temporary fixing film was irradiated with a UV-LED with a wavelength of 405nm (illuminance of 100mW / cm²) from the glass support component side. 2 Irradiation time: 50 seconds; cumulative light intensity: 5000 mJ / cm² 2 This process solidifies the temporary fixation film, resulting in a cured film.

[0196] Next, from the glass support component side, the obtained cured film is irradiated with a UV laser with a wavelength of 355nm (YAG laser, output 6.5W, spot diameter 150μm, irradiation spacing 200μm, scanning speed 8m / s, frequency 40kHz) in a scanning manner to obtain a laminate.

[0197] Next, 10 minutes after UV laser irradiation, the obtained laminate was placed on the adsorption stage with the silicon wafer side facing down and fixed in place. The adsorption arm, which is attached to the glass support component and has three 10 mm diameter suction cups, was vertically pulled upward at a speed of 0.5 mm / s to peel off the glass support component. The load applied to the adsorption arm when the glass support component was lifted was measured and set as the peel strength P2 (N).

[0198] (P2 / P1)

[0199] The ratio (P2 / P1) of the peel strength P2 of the temporary fixation composition of this embodiment based on method 5 after laser irradiation for 10 minutes to the peel strength P1 immediately after laser irradiation is preferably 3.0 or less, more preferably 2.5 or less, even more preferably 2.0 or less, and even more preferably 1.8 or less.

[0200] (Method 5)

[0201] A disk-shaped temporary fixing film (150mm in diameter × 625μm in thickness) composed of a temporary fixing composition is applied between a disk-shaped silicon wafer (150mm in diameter × 700μm in thickness) and a disk-shaped glass support member (150mm in diameter × 700μm in thickness), thereby bonding the silicon wafer and the glass support member together.

[0202] Next, under a nitrogen atmosphere, the temporary fixing film was irradiated with a UV-LED with a wavelength of 405nm (illuminance of 100mW / cm²) from the glass support component side. 2 Irradiation time: 50 seconds; cumulative light intensity: 5000 mJ / cm² 2 This process solidifies the temporary fixation film, resulting in a cured film.

[0203] Next, from the glass support component side, the obtained cured film is irradiated with a UV laser with a wavelength of 355nm (YAG laser, output 6.5W, spot diameter 150μm, irradiation spacing 200μm, scanning speed 8m / s, frequency 40kHz) in a scanning manner to obtain a laminate.

[0204] Next, within one minute after the UV laser irradiation ends, the obtained laminate is placed on the adsorption stage with the silicon wafer side facing down and fixed in place. The adsorption arm, which is attached to the glass support component and has three suction cups with a diameter of 10 mm, is vertically pulled upward at a speed of 0.5 mm / s to peel off the glass support component. The load applied to the adsorption arm when the glass support component is lifted is measured and set as the peel strength P1 (N).

[0205] Next, a laminate was obtained under the same conditions as described above. Ten minutes after UV laser irradiation was completed, the laminate was placed on an adsorption stage with the silicon wafer side facing down and fixed in place. An adsorption arm with three 10 mm diameter suction cups attached to a glass support was vertically pulled upward at a speed of 0.5 mm / s to peel off the glass support. The load applied to the adsorption arm when the glass support was lifted was measured and set as the peel strength P2 (N).

[0206] Calculate P2 / P1 based on P1 and P2 calculated using the method described above.

[0207] The temporary fixing composition of this embodiment is preferably capable of temporarily fixing the support component and the wafer.

[0208] The support component in this embodiment is not particularly limited, but a component that transmits light is preferred. This facilitates the removal of the wafer from light irradiation, such as UV laser irradiation. Examples of components that transmit light include inorganic substrates such as crystal, glass, quartz, calcium fluoride, and magnesium fluoride, as well as organic substrates such as plastics.

[0209] The support component in this embodiment is preferably one or more types selected from the group consisting of crystal support components and glass support components, and more preferably includes glass support components.

[0210] The wafer in this embodiment is preferably a semiconductor wafer.

[0211] 2. Chip manufacturing methods

[0212] The manufacturing method of the wafer according to this embodiment will be described below.

[0213] The wafer manufacturing method of this embodiment includes a peeling process in which a structure having a support member, a cured film of the temporary fixing composition of this embodiment, and a wafer are sequentially irradiated from the support member side with a UV laser with a wavelength of 300 nm or more and 385 nm or less, carbon particles are generated by decomposing at least a portion of the cured film of the temporary fixing composition, and the wafer and the support member are peeled off.

[0214] As described above, by using the temporary fixing composition of this embodiment to suppress the re-adhesion of the support member to the wafer, the reduction in workability can be suppressed even if there is a certain time interval between light irradiation such as UV laser irradiation and peeling.

[0215] From the viewpoint of further suppressing re-adhesion, the spot diameter of the UV laser in the stripping process is preferably 60 μm or more and 240 μm or less, more preferably 70 μm or more and 230 μm or less, even more preferably 80 μm or more and 220 μm or less, and even more preferably 90 μm or more and 210 μm or less.

[0216] From the viewpoint of further suppressing re-adhesion, the output of the UV laser in the stripping process is preferably 4.1W or more and 50.0W or less, more preferably 4.1W or more and 20.0W or less, even more preferably 4.1W or more and 15.0W or less, and even more preferably 4.2W or more and 10.0W or less.

[0217] From the viewpoint of improving manufacturing efficiency, the scanning speed of the UV laser in the peeling process of this embodiment is preferably 0.1 m / s or more, more preferably 1.0 m / s or more, even more preferably 2.0 m / s or more, and even more preferably 5.0 m / s or more. Furthermore, from the viewpoint of further suppressing re-adhesion, it is preferably 100 m / s or less, more preferably 50 m / s or less, even more preferably 20 m / s or less, and even more preferably 10 m / s or less. Moreover, from the viewpoint of balancing improved manufacturing efficiency and re-adhesion suppression, it is preferably 0.1 m / s or more and 100 m / s or less, more preferably 1.0 m / s or more and 50 m / s or less, even more preferably 2.0 m / s or more and 20 m / s or less, and even more preferably 5.0 m / s or more and 10 m / s or less.

[0218] The wafer manufacturing method of this embodiment preferably includes, prior to the stripping process, a thinning process of obtaining the structure (a) by thinning the wafer (b) in the structure (b) which sequentially includes a support member, a cured film of a temporary fixing composition and a wafer (b).

[0219] The wafer manufacturing method of this embodiment preferably includes, prior to the thinning process, a curing process in which a structure (c) having a support member, a temporary fixing film formed of a temporary fixing composition, and a wafer (b) in sequence is irradiated with light and the temporary fixing film is cured to obtain the structure (b).

[0220] The thickness of the cured film in this embodiment is preferably 0.1 μm or more and 500 μm or less, more preferably 1.0 μm or more and 200 μm or less, even more preferably 10 μm or more and 100 μm or less, and even more preferably 20 μm or more and 80 μm or less.

[0221] The cured film in this embodiment is preferably a single layer.

[0222] From the perspective of improving adhesion, the cumulative light intensity during the curing process is preferably 1000 mJ / cm. 2 From the perspective of improving productivity, the optimal value is 20000 mJ / cm³. 2 From the perspective of balancing improved adhesion and increased productivity, 1000 mJ / cm is preferred. 2 Above and 10000 mJ / cm 2 The preferred value is 3000 mJ / cm. 2 Above 8000mJ / cm 2 The following is a further preferred value: 4000 mJ / cm 2 Above and 6000mJ / cm 2 the following.

[0223] The embodiments of the present invention have been described above, but these are merely examples of the present invention, and various structures other than those described can be employed. Furthermore, the present invention is not limited to the above embodiments, and modifications and improvements within the scope of achieving the objectives of the present invention are included in the present invention.

[0224] Example

[0225] The present invention will be described in more detail below through embodiments, but the present invention is not limited to the embodiments.

[0226] Unless otherwise stated, the experiment was conducted at 23°C and 50% humidity.

[0227] (Preparation of the composition for temporary fixation)

[0228] The components (in parts by mass) shown in Tables 1 and 2 below were mixed at 60°C to obtain temporary fixation compositions for each example. The contents of each component are as follows.

[0229] The following was used as a polymeric component (A) containing (meth)acrylate.

[0230] A1 (a polybutyl acrylate containing acrylic acid groups, represented by the following chemical formula, with a weight-average molecular weight of 72,000)

[0231] [Chemical Formula 1]

[0232]

[0233] A-BPEF-2 (9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, product name: NK ESTER A-BPEF-2, manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.)

[0234] HBPE-4 (Ethoxylated hydrogenated bisphenol A diacrylate represented by the following chemical formula, product name: HBPE-4, manufactured by DKS Co. Ltd.)

[0235] [Chemical Formula 2]

[0236]

[0237] A-DOD-N (1,10-decanediol diacrylate, product name: A-DOD-N, manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.)

[0238] M-113 (nonylphenol ethylene oxide modified acrylate, with 4 ethylene oxide groups, product name: ARONIX M-113, manufactured by TOAGOSEI CO., LTD.)

[0239] ISTA (Isostearyl acrylate, product name: ISTA, manufactured by OSAKA ORGANIC CHEMICAL INDUSTRY LTD.)

[0240] The following was used as a photoradical polymerization initiator (B).

[0241] Omnirad 819 (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, product name: Omnirad 819, manufactured by IGM RESINS)

[0242] The following was used as an ultraviolet absorber (C).

[0243] RUVA-93 (2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, product name: RUVA-93, manufactured by Otsuka Chemical Co., Ltd.)

[0244] P-66 (2,2'-Dihydroxy-4,4'-Diacryloxybenzophenone, Product Name: DAINSORB P-66, Manufactured by Daiwa Fine Chemicals Co., Ltd.)

[0245] (Ratio of carbon particle generation area)

[0246] The ratio of the carbon particle generation area was determined using Method 1 described below. The results are shown in Tables 1 and 2 below. Furthermore, microscopic images of Example 1 and Comparative Example 3 are shown below. Figure 1 and Figure 2 middle.

[0247] (Method 1)

[0248] A disk-shaped temporary fixing film (150mm in diameter and 50μm in thickness) composed of a temporary fixing composition is applied between a disk-shaped silicon wafer (manufactured by Silicon Technology Co., Ltd., surface: mirror finish, conductivity type: P-type, diameter 150mm × thickness 625μm) and a disk-shaped glass support component (product name: Tempax glass, manufactured by OPC Corporation, diameter 150mm × thickness 700μm), thereby bonding the silicon wafer and the glass support component together.

[0249] Next, under a nitrogen atmosphere, the temporary fixing film was irradiated from the glass support component side with a UV-LED with a wavelength of 405nm (device name: LPDCJ1A-48102W, manufactured by ALTECH CO., LTD., illuminance 100mW / cm²). 2 Irradiation time: 50 seconds; cumulative light intensity: 5000 mJ / cm² 2 This process solidifies the temporary fixation film, resulting in a cured film.

[0250] Next, from the glass support component side, the obtained cured film was irradiated with a UV laser with a wavelength of 355nm (device name: TWD-D3000, manufactured by TAZMO CO., LTD., YAG laser, output 6.5W, spot diameter 150μm, irradiation spacing 200μm, scanning speed 8m / s, frequency 40kHz).

[0251] Next, the glass support component was peeled off from the silicon wafer, and the cured film side surface of the central part of the glass support component was observed and photographed at 20x magnification using an optical microscope (device name: MX-63L, manufactured by Evident Corporation). The area (%) of the black part in each field of view (200μm×200μm) was calculated using image processing software (product name: Fiji, manufactured by the National Institutes of Health) with the area of ​​one field of view (200μm×200μm) set to 100%, and this was taken as the area (%) of carbon particle generation.

[0252] (Viscosity)

[0253] Using a Type E viscometer (device name: DVNXHBCBG, manufactured by Brookfield Corporation, conical rotor product number: CPA-40Z, rotation speed: 10 rpm), at a temperature of 23°C and a shear rate of 75 s, the following was measured. -1 The viscosity of the temporary fixation composition was determined. The results are shown in Tables 1 and 2 below.

[0254] (Transmittance of a laser with a wavelength of 355nm)

[0255] The transmittance of the temporary fixation composition for a 355 nm wavelength laser was determined using method 2 described below. The results are shown in Tables 1 and 2 below.

[0256] (Method 2)

[0257] Prepare two rectangular Tempax glass pieces (33mm × 50mm, 700μm thick), drop 0.1g of the temporary fixation composition onto one of them, and clamp it with the other.

[0258] Next, the obtained laminate was irradiated with a UV-LED (405nm wavelength, device name: LPDCJ1A-48102W, manufactured by ALTECH CO., LTD., illuminance 100mW / cm²) under a nitrogen atmosphere. 2 Irradiation time: 50 seconds; cumulative light intensity: 5000 mJ / cm² 2 This process solidifies the temporary fixation composition, resulting in a test piece for transmittance measurement.

[0259] Next, the transmittance of the obtained test piece was measured using a spectrophotometer (device name: UV-2550, manufactured by Shimadzu Corporation) at a spacing of 1.0 nm and a wavelength range of 300–800 nm.

[0260] Next, the transmittance at wavelength 355nm is read from the obtained transmittance data and set as the transmittance at wavelength 355nm.

[0261] In addition, before the transmittance measurement, two rectangular Tempax glass pieces (33mm×50mm, 700μm thick) were prepared. 0.1g of water was dropped onto one of them and clamped with the other to obtain a baseline measurement test piece. The baseline of the spectrophotometer was measured using the obtained baseline measurement test piece.

[0262] (Peel strength P1 immediately after laser irradiation)

[0263] The peel strength P1 immediately after laser irradiation was determined using method 3 described below. The results are shown in Tables 1 and 2 below. Furthermore, the apparatus used for measuring the peel strength is shown. Figure 3 .

[0264] (Method 3)

[0265] A disk-shaped temporary fixing film (150mm in diameter and 50μm in thickness) composed of a temporary fixing composition is applied between a disk-shaped silicon wafer (manufactured by Silicon Technology Co., Ltd., surface: mirror finish, conductivity type: P-type, diameter 150mm × thickness 625μm) and a disk-shaped glass support component (product name: Tempax glass, manufactured by OPC Corporation, diameter 150mm × thickness 700μm), thereby bonding the silicon wafer and the glass support component together.

[0266] Next, under a nitrogen atmosphere, the temporary fixing film was irradiated with a UV-LED with a wavelength of 405nm (illuminance of 100mW / cm²) from the glass support component side. 2 Irradiation time: 50 seconds; cumulative light intensity: 5000 mJ / cm² 2 This process solidifies the temporary film, resulting in a cured film.

[0267] Next, from the glass support component side, the obtained cured film was irradiated with a UV laser with a wavelength of 355nm (device name: TWD-D3000, manufactured by TAZMO CO., LTD., YAG laser, output 6.5W, spot diameter 150μm, irradiation spacing 200μm, scanning speed 8m / s, frequency 40kHz) to obtain a laminate.

[0268] Next, within one minute after the UV laser irradiation ends, the obtained laminate is placed on the adsorption stage with the silicon wafer side facing down and fixed in place. The adsorption arm, which is attached to the glass support component and has three suction cups with a diameter of 10 mm, is vertically pulled upward at a speed of 0.5 mm / s to peel off the glass support component. The load applied to the adsorption arm when the glass support component is lifted is measured and set as the peel strength P1 (N).

[0269] (Peel strength P2 10 minutes after laser irradiation)

[0270] The peel strength P2 was determined using method 4 described below 10 minutes after laser irradiation. The results are shown in Tables 1 and 2 below.

[0271] (Method 4)

[0272] A disk-shaped temporary fixing film (150mm in diameter and 50μm in thickness) composed of a temporary fixing composition is applied between a disk-shaped silicon wafer (manufactured by Silicon Technology Co., Ltd., surface: mirror finish, conductivity type: P-type, diameter 150mm × thickness 625μm) and a disk-shaped glass support component (product name: Tempax glass, manufactured by OPC Corporation, diameter 150mm × thickness 700μm), thereby bonding the silicon wafer and the glass support component together.

[0273] Next, under a nitrogen atmosphere, the temporary fixing film was irradiated with a UV-LED with a wavelength of 405nm (illuminance of 100mW / cm²) from the glass support component side. 2 Irradiation time: 50 seconds; cumulative light intensity: 5000 mJ / cm² 2 This process solidifies the temporary fixation film, resulting in a cured film.

[0274] Next, from the glass support component side, the obtained cured film was irradiated with a UV laser with a wavelength of 355nm (device name: TWD-D3000, manufactured by TAZMO CO., LTD., YAG laser, output 6.5W, spot diameter 150μm, irradiation spacing 200μm, scanning speed 8m / s, frequency 40kHz) to obtain a laminate.

[0275] Next, 10 minutes after UV laser irradiation, the obtained laminate was placed on the adsorption stage with the silicon wafer side facing down and fixed in place. The adsorption arm, which is attached to the glass support component and has three 10 mm diameter suction cups, was vertically pulled upward at a speed of 0.5 mm / s to peel off the glass support component. The load applied to the adsorption arm when the glass support component was lifted was measured and set as the peel strength P2 (N).

[0276] (P2 / P1)

[0277] The ratio (P2 / P1) of the peel strength P2 10 minutes after laser irradiation to the peel strength P1 immediately after laser irradiation was determined using method 5 below. The results are shown in Tables 1 and 2 below.

[0278] (Method 5)

[0279] A disk-shaped temporary fixing film (150mm in diameter and 50μm in thickness) composed of a temporary fixing composition is applied between a disk-shaped silicon wafer (manufactured by Silicon Technology Co., Ltd., surface: mirror finish, conductivity type: P-type, diameter 150mm × thickness 625μm) and a disk-shaped glass support component (product name: Tempax glass, manufactured by OPC Corporation, diameter 150mm × thickness 700μm), thereby bonding the silicon wafer and the glass support component together.

[0280] Next, under a nitrogen atmosphere, the temporary fixing film was irradiated with a UV-LED with a wavelength of 405nm (illuminance of 100mW / cm²) from the glass support component side. 2 Irradiation time: 50 seconds; cumulative light intensity: 5000 mJ / cm² 2 This process solidifies the temporary fixation film, resulting in a cured film.

[0281] Next, from the glass support component side, the obtained cured film was irradiated with a UV laser with a wavelength of 355nm (device name: TWD-D3000, manufactured by TAZMO CO., LTD., YAG laser, output 6.5W, spot diameter 150μm, irradiation spacing 200μm, scanning speed 8m / s, frequency 40kHz) to obtain a laminate.

[0282] Next, within one minute after the UV laser irradiation ends, the obtained laminate is placed on the adsorption stage with the silicon wafer side facing down and fixed in place. The adsorption arm, which is attached to the glass support component and has three suction cups with a diameter of 10 mm, is vertically pulled upward at a speed of 0.5 mm / s to peel off the glass support component. The load applied to the adsorption arm when the glass support component is lifted is measured and set as the peel strength P1 (N).

[0283] Next, a laminate was obtained under the same conditions as described above. Ten minutes after UV laser irradiation was completed, the laminate was placed on an adsorption stage with the silicon wafer side facing down and fixed in place. An adsorption arm with three 10 mm diameter suction cups attached to a glass support was vertically pulled upward at a speed of 0.5 mm / s to peel off the glass support. The load applied to the adsorption arm when the glass support was lifted was measured and set as the peel strength P2 (N).

[0284] P2 / P1 was calculated from P1 and P2 obtained by the above method.

[0285] (Re-adhesion inhibition)

[0286] Re-adhesion inhibition was evaluated in three stages, A to C, using the following evaluation criteria. The results are shown in Tables 1 and 2 below.

[0287] A: P1 and P2 are both below 30.0N, and P2 / P1 is below 2.0.

[0288] B: P1 and P2 are both below 30.0 N, and P2 / P1 exceeds 2.0 N.

[0289] C: P1 and / or P2 exceed 30.0N, or cannot be desorbed.

[0290]

[0291]

[0292] In the temporary fixing composition of the embodiment, the evaluation results for re-adhesion suppression based on the above evaluation criteria are good. That is, in the temporary fixing composition of the embodiment, re-adhesion between the wafer and the support member after a certain period of time following laser irradiation is suppressed. Therefore, it can be seen that the temporary fixing composition according to this embodiment can suppress re-adhesion between the wafer and the support member after a certain period of time following laser irradiation.

[0293] This application claims priority based on Japanese Patent Application No. 2024-050950, filed on March 27, 2024, the entire contents of which are incorporated herein by reference.

Claims

1. A composition for temporary fixation, comprising: Polymerizing component (A) containing (meth)acrylate. Photoradical polymerization initiator (B), and Ultraviolet absorber (C); The ratio of carbon particle generation area based on Method 1 below is 0.50% or higher. Method 1: A temporary fixing film, consisting of the aforementioned temporary fixing composition, is applied between a disk-shaped silicon wafer with a diameter of 150 mm and a thickness of 625 μm and a disk-shaped glass support member with a diameter of 150 mm and a thickness of 700 μm, thereby bonding the silicon wafer and the glass support member together. Next, under a nitrogen atmosphere, a UV-LED with a wavelength of 405 nm is irradiated onto the temporary fixing film from the glass support component side, thereby curing the temporary fixing film to obtain a cured film. The illuminance of the UV-LED is 100mW / cm². 2 The irradiation time was 50 seconds, and the cumulative light intensity was 5000 mJ / cm². 2 , Next, from the glass support component side, the obtained cured film is irradiated with a 355nm UV laser in a scanning manner, wherein the UV laser is a YAG laser with an output of 6.5W, a spot diameter of 150μm, an irradiation spacing of 200μm, a scanning speed of 8m / s, and a frequency of 40kHz. Next, the glass support component is peeled off from the silicon wafer, and the solidified film side surface of the central part of the glass support component is observed and photographed using an optical microscope at 20x magnification. The area (%) of the black part in each field of view is calculated using image processing software when the area of ​​one field of view of 200μm×200μm is set to 100%, and this is taken as the carbon particle generation area (%).

2. The composition for temporary fixation according to claim 1, wherein, The carbon particles contain carbon black.

3. The temporary fixation composition according to claim 1 or 2, wherein, The carbon particle content in the temporary fixation composition is less than 1.0% by mass.

4. The temporary fixation composition according to claim 1 or 2, wherein, The photoradical polymerization initiator (B) comprises one or more selected from the group consisting of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl] acetone 1-(O-acetyl oxime).

5. The temporary fixation composition according to claim 1 or 2, wherein, The ultraviolet absorber (C) has one or more skeletons selected from the group consisting of benzophenone skeleton, triazole skeleton, hydroxyphenyltriazine skeleton and phenol skeleton.

6. The temporary fixation composition according to claim 1 or 2, wherein, The ultraviolet absorber (C) has polymerizable functional groups.

7. The temporary fixation composition according to claim 6, wherein, The polymeric functional group is present at the end of the ultraviolet absorber (C).

8. The temporary fixation composition according to claim 6, wherein, The polymerizable functional group includes (meth)acryloyl.

9. The temporary fixation composition according to claim 1 or 2, wherein, The content of the ultraviolet absorber (C) is 0.1 parts by mass or more and 20 parts by mass or less, relative to 100 parts by mass of the polymeric component (A) containing (meth)acrylate.

10. The temporary fixation composition according to claim 1 or 2, wherein, The content of the polymeric component (A) containing (meth)acrylate is 50% by mass or more and 99% by mass or less relative to 100% by mass of the temporary fixation composition.

11. The temporary fixation composition according to claim 1 or 2, wherein, The content of the photoradical polymerization initiator (B) is 0.1 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the polymerizable component (A) containing (meth)acrylate.

12. The temporary fixation composition according to claim 1 or 2, wherein, The polymeric component (A) containing (meth)acrylate comprises one or more selected from the group consisting of monofunctional (meth)acrylates and difunctional (meth)acrylates.

13. The temporary fixation composition according to claim 1 or 2, wherein, The polymeric component (A) containing (meth)acrylate comprises one or more selected from the group consisting of monofunctional alkyl (meth)acrylates having an alkyl group, aromatic (meth)acrylates, alicyclic difunctional (meth)acrylates and noncyclic difunctional (meth)acrylates.

14. The temporary fixation composition according to claim 13, wherein, The aromatic (meth) acrylate contains a component selected from 9,9-bis[4-(2-hydroxyC1-C1-C2-hydroxyethyl esters). 20 [Alkoxy]phenyl]fluorene di(meth)acrylate, 9,9-bis[4-(2-(meth)acryloyloxyC1~C 20 [alkoxy]phenyl]fluorene, C1-C 20 Alkoxylated bisphenol A di(meth)acrylate, benzyl di(meth)acrylate, 1,3-bis(2-(meth)acryloyloxy C1-C 20 One or more of the following groups: alkyl)benzene, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, nonylphenol ethylene oxide-modified (meth)acrylate and their structural isomers.

15. The temporary fixation composition according to claim 1 or 2, wherein, Using an E-type viscometer, at a temperature of 23°C and a shear rate of 75s... -1 The viscosity of the temporary fixation composition, as measured below, is 100 mPa•s or more and 5000 mPa•s or less.

16. The temporary fixation composition according to claim 1 or 2, wherein, When implementing method 2 below, the transmittance of the 355nm wavelength laser is less than 10.0%. Method 2: Prepare two rectangular Tempax glass sheets, each 33mm × 50mm in diameter and 700μm thick. Place 0.1g of the temporary fixation composition onto one sheet and clamp it with the other. Next, the obtained laminate was irradiated with a UV-LED at a wavelength of 405 nm under a nitrogen atmosphere, thereby curing the temporary fixing composition to obtain a test piece for transmittance measurement, wherein the illuminance of the UV-LED was 100 mW / cm². 2 The irradiation time was 50 seconds, and the cumulative light intensity was 5000 mJ / cm². 2 , Next, the transmittance of the obtained test piece was measured using a spectrophotometer at a spacing of 1.0 nm and a wavelength range of 300–800 nm. Next, the transmittance at wavelength 355nm is read from the obtained transmittance data and set as the transmittance at wavelength 355nm.

17. The temporary fixation composition according to claim 1 or 2, wherein, The peel strength P1 immediately after laser irradiation based on method 3 is above 0.01 N and below 30.0 N. Method 3: A temporary fixing film, consisting of the aforementioned temporary fixing composition, is applied between a disk-shaped silicon wafer with a diameter of 150 mm and a thickness of 625 μm and a disk-shaped glass support member with a diameter of 150 mm and a thickness of 700 μm, thereby bonding the silicon wafer and the glass support member together. Next, under a nitrogen atmosphere, a UV-LED with a wavelength of 405 nm is irradiated onto the temporary fixing film from the side of the glass support component, thereby curing the temporary fixing film to obtain a cured film, wherein the illuminance of the UV-LED is 100 mW / cm². 2 The irradiation time was 50 seconds, and the cumulative light intensity was 5000 mJ / cm². 2 , Next, from the glass support component side, the obtained cured film is irradiated with a UV laser with a wavelength of 355nm in a scanning manner to obtain a laminate. The UV laser is a YAG laser with an output of 6.5W, a spot diameter of 150μm, an irradiation spacing of 200μm, a scanning speed of 8m / s, and a frequency of 40kHz. Next, within one minute after the UV laser irradiation ends, the obtained laminate is placed on the adsorption stage with the silicon wafer side facing down and fixed. An adsorption arm with three 10mm diameter suction cups attached to the glass support component is vertically pulled upward at a speed of 0.5mm / second to peel off the glass support component. The load applied to the adsorption arm when the glass support component is lifted is measured and set as the peel strength P1 (N).

18. The temporary fixation composition according to claim 1 or 2, wherein, Based on method 4 below, the peel strength P2 10 minutes after laser irradiation is greater than 0.01N and less than 50.0N. Method 4: A temporary fixing film, consisting of the aforementioned temporary fixing composition, is applied between a disk-shaped silicon wafer with a diameter of 150 mm and a thickness of 625 μm and a disk-shaped glass support member with a diameter of 150 mm and a thickness of 700 μm, thereby bonding the silicon wafer and the glass support member together. Next, under a nitrogen atmosphere, a UV-LED with a wavelength of 405 nm is irradiated onto the temporary fixing film from the side of the glass support component, thereby curing the temporary fixing film to obtain a cured film, wherein the illuminance of the UV-LED is 100 mW / cm². 2 The irradiation time was 50 seconds, and the cumulative light intensity was 5000 mJ / cm². 2 , Next, from the glass support component side, the obtained cured film is irradiated with a UV laser with a wavelength of 355nm in a scanning manner to obtain a laminate. The UV laser is a YAG laser with an output of 6.5W, a spot diameter of 150μm, an irradiation spacing of 200μm, a scanning speed of 8m / s, and a frequency of 40kHz. Next, 10 minutes after UV laser irradiation, the obtained laminate was placed on the adsorption stage with the silicon wafer side facing down and fixed in place. An adsorption arm with three 10mm diameter suction cups attached to the glass support component was vertically pulled upward at a speed of 0.5mm / second to peel off the glass support component. The load applied to the adsorption arm when the glass support component was lifted was measured and set as the peel strength P2 (N).

19. The temporary fixation composition according to claim 1 or 2, wherein, Based on the following method 5, the ratio of the peel strength P2 10 minutes after laser irradiation to the peel strength P1 immediately after laser irradiation, i.e., P2 / P1, is less than 2.

0. Method 5: A temporary fixing film, consisting of the aforementioned temporary fixing composition, is applied between a disk-shaped silicon wafer with a diameter of 150 mm and a thickness of 625 μm and a disk-shaped glass support member with a diameter of 150 mm and a thickness of 700 μm, thereby bonding the silicon wafer and the glass support member together. Next, under a nitrogen atmosphere, a UV-LED with a wavelength of 405 nm is irradiated onto the temporary fixing film from the side of the glass support component, thereby curing the temporary fixing film to obtain a cured film, wherein the illuminance of the UV-LED is 100 mW / cm². 2 The irradiation time was 50 seconds, and the cumulative light intensity was 5000 mJ / cm². 2 , Next, from the glass support component side, the obtained cured film is irradiated with a UV laser with a wavelength of 355nm in a scanning manner to obtain a laminate. The UV laser is a YAG laser with an output of 6.5W, a spot diameter of 150μm, an irradiation spacing of 200μm, a scanning speed of 8m / s, and a frequency of 40kHz. Next, within one minute of the end of UV laser irradiation, the obtained laminate was placed on the adsorption stage with the silicon wafer side facing down and fixed in place. An adsorption arm with three 10mm diameter suction cups attached to the glass support component was vertically pulled upward at a speed of 0.5mm / second to peel off the glass support component. The load applied to the adsorption arm when lifting the glass support component was measured and set as the peel strength P1 (N). Next, a laminate was obtained under the same conditions as described above. Ten minutes after UV laser irradiation, the laminate was placed on an adsorption stage with the silicon wafer side facing down and fixed in place. An adsorption arm with three 10mm diameter suction cups attached to the glass support was vertically pulled upward at a speed of 0.5mm / s to peel off the glass support. The load applied to the adsorption arm when lifting the glass support was measured and set as the peel strength P2 (N). Calculate P2 / P1 based on P1 and P2 calculated using the method described above.

20. The temporary fixing composition according to claim 1 or 2, which is capable of temporarily fixing the support member and the wafer.

21. The temporary fixation composition according to claim 20, wherein, The supporting components include glass supporting components.

22. The temporary fixation composition according to claim 20, wherein, The wafer includes a semiconductor wafer.

23. A method for manufacturing a wafer, comprising: In the peeling process, a structure having a support member, a cured film of the temporary fixing composition according to claim 1 or 2, and a wafer are sequentially irradiated from the support member side with a UV laser with a wavelength of 300 nm or more and 385 nm or less. Carbon particles are generated by decomposing at least a portion of the cured film of the temporary fixing composition, and the wafer and the support member are peeled off.

24. A composition comprising: Polymerizing component (A). Polymerization initiator (B), and Ultraviolet absorber (C); The ratio of carbon particle generation area based on Method 1 below is 0.50% or higher. Method 1: A disk-shaped film, consisting of the aforementioned composition, with a diameter of 150 mm and a thickness of 625 μm, is applied between a disk-shaped silicon wafer and a disk-shaped glass support member with a diameter of 150 mm and a thickness of 700 μm, thereby bonding the silicon wafer and the glass support member together. Next, under a nitrogen atmosphere, the film is irradiated with a UV-LED with a wavelength of 405 nm from the glass support member side, thereby curing the film to obtain a cured film. The illuminance of the UV-LED is 100mW / cm². 2 The irradiation time was 50 seconds, and the cumulative light intensity was 5000 mJ / cm². 2 , Next, from the glass support component side, the obtained cured film is irradiated with a 355nm UV laser in a scanning manner, wherein the UV laser is a YAG laser with an output of 6.5W, a spot diameter of 150μm, an irradiation spacing of 200μm, a scanning speed of 8m / s, and a frequency of 40kHz. Next, the glass support component is peeled off from the silicon wafer, and the solidified film side surface of the central part of the glass support component is observed and photographed using an optical microscope at 20x magnification. The area (%) of the black part in each field of view is calculated using image processing software when the area of ​​one field of view of 200μm×200μm is set to 100%, and this is taken as the carbon particle generation area (%).

Citation Information

Patent Citations

  • Resin composition for cladding optical fiber

    JP1986031330A

  • Resin and resin composition for sealant

    JP1986207478A

  • Photocurable urethane acrylate oligomer and photocurable composition

    JP1997040741A

  • Thermally bondable film and processing material to be covered

    JP1998278207A

  • Multi-amine polyester dispersant and method of making

    JP2024050950A